Dynamic process intensification of binary distillation based on output multiplicity. Issue 4 (10th January 2019) - Yan, Lingqing; Edgar, Thomas F.; Baldea, Michael
Abstract : Process intensification focuses largely on process and equipment design . Much less emphasis has been placed on operational changes to achieve cost savings and increased efficiency. This article introduces the concept of dynamic intensification, defined as changes to the dynamics, operating strategy and/or control of a process that lead to a substantially more efficient processing path. This idea is illustrated in the context of binary distillation. Output multiplicity properties are exploited to establish a new periodic operating mode based on switching between two auxiliary products, which, on a time‐average basis, is more energy efficient than steady‐state operation. An extensive case study is presented concerning the distillation of a propanol–acetic acid mixture, confirming the theoretical developments. In contrast to previous research (e.g., on cyclic distillation), the present concept has significant advantages as it relies on existing hardware and exploiting system nonlinearity, rather than using specialized equipment operated in a discontinuous fashion. © 2018 American Institute of Chemical Engineers AIChE J, 65: 1162–1172, 2019